2022
DOI: 10.1186/s41235-022-00402-9
|View full text |Cite
|
Sign up to set email alerts
|

Two face masks are better than one: congruency effects in face matching

Abstract: Although the positive effects of congruency between stimuli are well replicated in face memory paradigms, mixed findings have been found in face matching. Due to the current COVID-19 pandemic, face masks are now very common during daily life outdoor activities. Thus, the present study aims to further explore congruency effects in matching faces partially occluded by surgical masks. Observers performed a face matching task consisting of pairs of faces presented in full view (i.e., full-view condition), pairs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…First, we did not account for congruency effects between face learning and face recognition. Previous research has shown the importance of congruency in face identification 56 58 . For example, faces learned with a ski mask are better recognized when they are also presented with a ski mask compared to full-view faces 57 .…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not account for congruency effects between face learning and face recognition. Previous research has shown the importance of congruency in face identification 56 58 . For example, faces learned with a ski mask are better recognized when they are also presented with a ski mask compared to full-view faces 57 .…”
Section: Discussionmentioning
confidence: 99%
“…With the increased use of surgical face masks because of the COVID-19 pandemic, several authors have explored how surgical face masks affect face identification [42][43][44][45][46]. For example, Carragher and Hancock [44] adapted the Glasgow Face Matching Test [21] to study the effect of masks on simultaneous face matching (see also [43,45,46]). Despite the simultaneous presentation of both faces, face masks also disrupted performance in face matching.…”
Section: Introductionmentioning
confidence: 99%